Peran Kebiasaan Membaca Label dalam Memediasi Pengaruh Variabel Demografi terhadap Niat Membeli Produk Hijau Merek Natur-E di Kota Denpasar - Putri, Yuliana; Suparna, Gede (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
As for the purpose of this research is to determine the role of reading labels to mediate the effect of demographic variables on purchase intention green product Natur-E in Denpasar. Number of samples of this study was 100 respondents who been through certain criteria. Based on Baron and Kenny Steps and Sobel Test demographic has positive on purchase intention and reading label, and then reading label has positive on purchase intention green product Natur-E in Denpasar. This study also showed that reading label mediate positive demographic on purchase intention green product Natur-E in Denpasar.
Keywords: reading label, demographic, purchase intention